Latin America : Highlights from the Implementation of the System of National Accounts 1993 (1993 SNA) - Ramos, Roberto (IMF Working Papers; Working Paper ;, 2008)
This paper reviews the Latin American experience with the implementation of 1993 SNAand the updating of the national accounts' base year. It also makes a preliminary assessment of the possible estimation biases in nominal GDP estimates stemming from the use of outdated national accounts base years, downwards biases with household final consumption estimates, and an overestimation of gross fixed capital formation in construction activities.